(untitled) (Defense and Security Studies, 2022)
Because of their high lethality and easy way to produce, abrin and ricin are often used as bioweapons. Sources of raw materials for the abrin and ricin manufacture can be found in various regions, especially in tropical countries. Those make abrin and ricin have a greater chance to be used as bioterrorism agents. Furthermore, abrin and ricin have been classified as class B types of bioweapons used in bioterrorism. In this study, a virtual screening (a bioinformatics method) will be carried out on 100 compounds derived from Indonesian Plants. Thus it can be known, the compounds that have the potential to be used as biodefense agents against abrin and ricin. Finally, it is found that there are five compounds that have the best possibility as abrin inhibitors: procyanidin B4, ursolic acid, Corilagin, Vulgarin, and Gliberelic Acid. Whereas lanuginosine, xylonine, isovitexin, liriodenine, and procyanidin were found to have more potential as biodefense agents against ricin.